Digital Simulacra Construction of a Digital Product Creator: A Study of Lynk.id Utilization on the Instagram Account @abdulaziz.writer - Ina Yatun Khoiriyah; Merlia Indah Pratiwi (Communigate, 2025)
The rapid expansion of digital platforms has transformed how identity, authority, and economic value are constructed within the creative economy. This study examines the construction of digital simulacra by a digital product creator through the monetization platform Lynk.id on the Instagram account @abdulaziz.writer. Drawing on Jean Baudrillard’s theory of simulacra and hyperreality, this research aims to analyze how symbolic representation, personal branding, and platform architecture shape audience perception and economic legitimacy. A qualitative phenomenological approach was employed. Data were collected through online observation, documentation of digital content, and in-depth interviews with the account owner and six digital product users. The findings reveal that the creator strategically constructs a professional digital identity through consistent educational and motivational narratives, minimalist visual design, and testimonial-based validation. These symbolic strategies generate a condition of hyperreality in which audiences perceive the digital persona as more authentic and credible than empirical reality. Lynk.id functions not merely as a transactional tool but as a simulation space that amplifies symbolic capital and economic value. This study contributes to digital sociology by demonstrating that in contemporary platform capitalism, economic legitimacy is increasingly produced through the circulation of signs rather than material verification.